Laboratory diagnosis for human chimerism: systematic review (Research, Society and Development, 2022)
The objective of the article was to perform a systematic review of the literature on laboratory diagnosis for human chimerism. The Medical Literature Analysis and Retrieval System Online (Medline), Public Medline or Publisher Medline (PubMed), Scientific Electronic Library (Scielo), Latin American and Caribbean Literature on Health Sciences (LILACS) databases were searched according to the Preferred Reporting Items for Systematic Reviews and Meta-Analyses (PRISMA) methodology. Articles were included that had as an endpoint evidencing the diagnosis for chimerism in humans, published in the period from 2005 to 2018. Articles whose endpoint was the occurrence of other types of chimerism were excluded. To compose the study, 36 articles were pre-selected, of these only 6 met the inclusion criteria given by the PRISMA method. Regarding the diagnostics used in the articles to detect chimerism, in 100% of the articles there is reference to the Polymerase Chain Reaction (PCR) combined with other techniques as the main diagnostic for detection of chimerism, such as Fluorescent in situ hybridization (FISH), Short Tandem Repeats (STR), Single Nucleotide Polymorphisms (SNPs), Small Insertions and Deletions (INDELs), Single Molecular Inversion Molecular Probes (smMIP) and TaqMan type molecular probes. These combined techniques have many advantages and are decisive for the scientific community in revealing this genetic condition. Thus, it is concluded that there are few techniques that allow a specific diagnosis for chimerism, however, the existing techniques are effective in identifying this genetic condition.